Continuous thermosalinograph oceanography along RV MARIA S. MERIAN cruise track MSM133 - Michael Schlundt; Morten Hvitfeldt Iversen (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 6 hours. While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. Neither temperature nor salinity calibration was performed. For details to all processing steps see Data Processing Report.